A practical approach to immunohistochemical diagnosis of ovarian germ cell tumours and sex cord–stromal tumours. Issue 1 (13th December 2012) - Rabban, Joseph T; Zaloudek, Charles J
Abstract : Immunohistochemistry can be useful in the diagnosis of ovarian germ cell tumours and sex cord–stromal tumours. A wide variety of markers are available, including many that are novel. The aim of this review is to provide a practical approach to the selection and interpretation of these markers, emphasizing an understanding of their sensitivity and specificity in the particular differential diagnosis in question. The main markers discussed include those for malignant germ cell differentiation (SALL4 and placental alkaline phosphatase), dysgerminoma (OCT4, CD117, and D2‐40), yolk sac tumour (α‐fetoprotein and glypican‐3), embryonal carcinoma (OCT4, CD30, and SOX2), sex cord–stromal differentiation (calretinin, inhibin, SF‐1, FOXL2) and steroid cell tumours (melan‐A). In addition, the limited role of immunohistochemistry in determining the primary site of origin of an ovarian carcinoid tumour is discussed.